2020
DOI: 10.2147/ott.s274744
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-1297 Suppresses Osteosarcoma Proliferation and Aerobic Glycolysis by Regulating PFKFB2</p>

Abstract: Background MiR-1297 is reported to function as a tumor suppressor of various cancers. However, the role of miR-1297 in the development of osteosarcoma (OS) has not been elaborated. The purpose of this study was to investigate the functional effects of miR-1297 on OS progression and the underlying mechanism. Methods The expression of protein and mRNA in OS cells was evaluated by Western blotting and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The aerobic glycolysis is essential to meet the metabolic requirements of cancer cell proliferation [ 9 ]. This is also true for OS cells, since suppression of the glycolytic process has been correlated with blocked tumor growth, survival, and metastasis [ 25 ]. In this research, we confirmed that the KDM3A-SP1 axis-mediated PFKFB4 upregulation promoted aerobic glycolysis in OS and augmented tumor cell growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The aerobic glycolysis is essential to meet the metabolic requirements of cancer cell proliferation [ 9 ]. This is also true for OS cells, since suppression of the glycolytic process has been correlated with blocked tumor growth, survival, and metastasis [ 25 ]. In this research, we confirmed that the KDM3A-SP1 axis-mediated PFKFB4 upregulation promoted aerobic glycolysis in OS and augmented tumor cell growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The recently discovered lncRNA LINC01123 was initially identified as an oncogene in non‐small cell lung cancer (NSCLC) 8 . Accumulating evidence indicates that LINC01123 promotes tumor growth in various cancers 6,9 . However, the function of LINC01123 in OS remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are defined as small endogenous molecules without protein-coding ability and can have an important role in cancer progression [43,44]. For example, miR-1297 was reported to suppress OS proliferation by regulating PFKFB2 [45]. MiR-365a-3p is also a critical participant in regulating cancer growth.…”
Section: Discussionmentioning
confidence: 99%